Integrative analysis of microRNAs and mRNAs reveals the regulatory networks of triterpenoid saponin metabolism in Soapberry (Sapindus mukorossi Gaertn.) - Xu, Yuanyuan; Liu, Jiming; Ji, Xiangqin; Zhao, Guochun; Zhao, Tianyun; Wang, Xin; Wang, Lixian; Gao, Shilun; Hao, Yingying; Gao, Yuhan; Gao, Yuan; Weng, Xuehuang; et al. (Frontiers in Plant Science, 2023)
Triterpenoid saponin are important secondary metabolites and bioactive constituents of soapberry (Sapindus mukorossi Gaertn.) and are widely used in medicine and toiletry products. However, little is known about the roles of miRNAs in the regulation of triterpenoid saponin biosynthesis in soapberry. In this study, a total of 3036 miRNAs were identified, of which 1372 miRNAs were differentially expressed at different stages of pericarp development. Important KEGG pathways, such as terpenoid backbone biosynthesis, sesquiterpenoid and triterpenoid biosynthesis, and basal transcription factors were highlighted, as well the roles of some key miRNAs, such as ath-miR5021, han-miR3630-3p, and ppe-miR858, which may play important roles in regulating triterpenoid saponin biosynthesis. In addition, 58 miRNAs might participate in saponin biosynthesis pathways by predicting the targets of those miRNAs to 53 saponin biosynthesis structural genes. And 75 miRNAs were identified to potentially play vital role in saponin accumulation by targeting transcript factor genes, bHLH, bZIP, ERF, MYB, and WRKY, respectively, which are candidate regulatory genes in the pathway of saponin biosynthesis. The results of weighted gene coexpression network analysis (WGCNA) suggested that two saponin-specific miRNA modules and 10 hub miRNAs may participate in saponin biosynthesis. Furthermore, multiple miRNA–mRNA regulatory networks potentially involved in saponin biosynthesis were generated, e.g., ath-miR5021–SmIDI2/SmGPS5/SmbAS1/SmCYP71D-3/SmUGT74G-2, han-miR3630-3p–SmCYP71A-14/SmbHLH54/SmMYB135/SmWRKY32, and ppe-miR858–SmMYB5/SmMYB32. qRT-PCR analysis validated the expression patterns of nine miRNAs and 12 corresponding target genes. This study represents the first comprehensive analysis of miRNAs in soapberry and lays the foundation for further understanding of miRNA-based regulation in triterpenoid saponin biosynthesis.